Efficient one-pot synthesis of unsymmetrical gold(I) N-heterocyclic carbene complexes and their use as catalysts - Hashmi, A. Stephen K.; Yu, Yang; Rominger, Frank (Organometallics, 2012)
Eleven different gold(I) complexes of new NHC ligands were prepared in excellent yield, demonstrating the versatility of the new route to NHC complexes. While the influence of electronically different ligands on the synthesis of the catalysts was small, the catalytic activities of the products differed significantly.
Gesehen am 06.09.2018